Autoimmunity in MFG-E8–deficient mice is associated with altered trafficking and enhanced cross-presentation of apoptotic cell antigens - Peng, YuFeng; Elkon, Keith B. (The Journal of Clinical Investigation, 2011)
Apoptotic cells must be rapidly cleared, as defects in this process can lead to autoimmunity. Milk fat globule EGF factor 8 (MFG-E8) binds to apoptotic cells and facilitates their removal through interaction with phagocytes. Mice deficient in MFG-E8 develop lupus-like autoimmunity associated with accumulation of apoptotic cells in vivo. Here, we have shown that MFG-E8 controls phagocytic ingestion of cell fragments as well as their intracellular processing into MHC-antigen complexes. Older Mfge8–/– mice spontaneously developed dermatitis associated with CD8+ T cell infiltration and striking activation of effector memory CD8+ T cells. CD8+ T cell responses to both exogenous and endogenous apoptotic cell–associated antigens were enhanced in Mfge8–/– mice. MFG-E8 deficiency accelerated the onset of disease in a mouse model of autoimmune diabetes. Enhanced CD8+ T cell responses were attributed to increased cross-presentation by DCs along with increased detection of antigen-MHCI complexes. Intracellular trafficking analysis revealed that intact apoptotic cells ingested by wild-type DCs rapidly fused with lysosomes, whereas smaller fragments persisted in Mfge8–/– DC endosomal compartments for 24 hours. These observations suggest that MFG-E8 deficiency promotes immune responses to self antigens not only by delaying the clearance of dying cells but also by altering intracellular processing, leading to enhanced self-antigen presentation.